2017
DOI: 10.1111/nph.14602
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in water availability mediate plant–pollinator interactions

Abstract: Summary Altered precipitation patterns associated with anthropogenic climate change are expected to have many effects on plants and insect pollinators, but it is unknown if effects on pollination are mediated by changes in water availability. We tested the hypothesis that impacts of climate on plant–pollinator interactions operate through changes in water availability, and specifically that such effects occur through alteration of floral attractants. We manipulated water availability in two naturally occurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(152 citation statements)
references
References 67 publications
10
137
4
1
Order By: Relevance
“…For flowers that did contain nectar, drought had no effect on the volume or sugar concentration of that nectar. This is contrary to our first and second hypotheses and contrasts with many previous studies that have demonstrated changes in nectar volume in response to water availability (Carroll et al., ; Gallagher & Campbell, ; Lee & Felker, ; Villarreal & Freeman, ; Wyatt et al., ; Zimmerman & Pyke, ). It is possible that the reduction in soil moisture content in this experiment (approximately 10% reduction in soil moisture content immediately after drought period) was not great enough to induce nectar volume changes.…”
Section: Discussioncontrasting
confidence: 99%
“…For flowers that did contain nectar, drought had no effect on the volume or sugar concentration of that nectar. This is contrary to our first and second hypotheses and contrasts with many previous studies that have demonstrated changes in nectar volume in response to water availability (Carroll et al., ; Gallagher & Campbell, ; Lee & Felker, ; Villarreal & Freeman, ; Wyatt et al., ; Zimmerman & Pyke, ). It is possible that the reduction in soil moisture content in this experiment (approximately 10% reduction in soil moisture content immediately after drought period) was not great enough to induce nectar volume changes.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, we tested for differences in seed set among flowers visited by different insect types, including bumblebee vs. solitary bee, and the average for bees vs. flies. Mertensia ciliata is traditionally described as a bumblebee‐pollinated species (Pelton, ; Geber, ; Suzuki, ; Gallagher and Campbell, ), therefore, we expected single bumblebee visits would produce more seeds than visits by solitary bees. We hypothesized that bee‐pollinated flowers (bumblebees, solitary bees, and combination) would produce more seeds than flowers visited by flies, because bees foraging for pollen and nectar are likely to move more outcross pollen among plants than flies, which stay for extended periods in the same flower or among flowers on the same plant (Forrest et al., ; Bischoff et al., ; Gallagher, personal observation).…”
Section: Methodsmentioning
confidence: 99%
“…Another fundamental route by which environmental change can alter plant–pollinator interactions is by influencing floral cues important for pollinator attraction (Schweiger et al ., ; Hoover et al ., ; Scaven & Rafferty, ; Burkle & Runyon, ). For example, water availability can strongly influence flower size, nectar volume, floral scent, pollinator visitation rates and pollinator community composition for several plant species (Carroll et al ., ; Burkle & Runyon, ; Gallagher & Campbell, ). Thus, examining how floral traits, pollinator visitation rates and pollinator community composition are affected by climate factors is key to understanding and predicting how global change will impact pollination services.…”
Section: Introductionmentioning
confidence: 99%